The Relationship between Religion and Reason in the Context of Islamic Education Philosophy from the Perspective of Ibn Rushd and Ibn Taimiyah - Lalahwa, Illa Fadhliya; Gunawan, Agus; Muhajir, Muhajir (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This article examines the thoughts of prominent philosophers Ibnu Rushd and Ibnu Taymiyah in terms of the relationship between religion and reason in the context of Islamic educational philosophy from the perspective of Ibn Rushd and Ibn Taymiyah. The purpose of this article is to provide readers with an understanding of the relationship between religion and reason in the context of Islamic educational philosophy. This research method uses the library research method or library study. The conclusion that can be drawn from Ibn Rushd is that being busy with philosophy does not make faith and religion damaged. Because philosophy does not conflict with religion, while religion does not deny philosophy, in fact it recommends and calls for it, because religion commands research and contemplation of the universe. In general, philosophizing is nothing more than examining forms in terms of their indication of the existence of a Creator. Ibn Taimiyah emphasized that in principle revelation and reason cannot conflict with each other. And if it is forced, there will be a conflict between the two, the conflict that arises is the argument, namely about the status of qat'i zanni, not about its status as revelation and reason.